Evaluation of the Brazilian Cosmetic Legislation and its impact on the industries during the 20th century - Wanessa Almeida Ciancaglio Garbossa; Patrícia Maria Berardo Gonçalves Maia Campos
ABSTRACT Cosmetics have been used since the very first days of human life. This early and continuing consumption has resulted in the growth of the Cosmetic Industry (C.I.). The C.I. must continue to invest in the development of innovative products which are safe for the consumers. On the other hand, the Health Agency should issue laws regulating the development of products. Thus, the aim of this study was to evaluate the Brazilian Cosmetic Legislation before ANVISA and the challenges for the C.I. during the 20th century regarding the development of safe and effective cosmetics, and to show the importance of this legislation in the R&D. A Bibliographic and Documentary Exploratory Research was conducted based on safety and efficacy data contained in scientific studies and legal documents. The study showed that the creation of ANVISA was necessary because no resolution had been published about the safety and efficacy of cosmetics for the C.I. before ANVISA. However, the challenges faced by the C.I. may have had a negative impact on the health of consumers. Finally, it was concluded that the actions before ANVISA were insufficient to the C.I.. Thus, the creation of ANVISA was essential to have a regulatory basis fot the C.I.